2018
DOI: 10.1186/s12711-018-0417-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic selection against intrauterine growth retardation in piglets: a problem at the piglet level with a solution at the sow level

Abstract: BackgroundIn polytocous livestock species, litter size and offspring weight act antagonistically; in modern pig breeds, selection for increased litter size has resulted in lower mean birth weights, an increased number of small piglets and an increased number of those affected by varying degrees of intrauterine growth retardation (IUGR). IUGR poses life-long challenges, both mental, with morphological brain changes and altered cognition, and physical, such as immaturity of organs, reduced colostrum intake and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 90 publications
6
50
0
Order By: Relevance
“…A recent study found that the relative abundance of Firmicutes is associated with energy intake from the diet (Turnbaugh et al ); a higher proportion of the Firmicutes phylum was found in obese children and adults than lean individuals. In the present study, the lower relative abundance of Bacteroidetes and Firmicutes in IUGR piglets than controls suggests that IUGR piglets are less efficient at extracting energy from their diet and consequently gain less weight (Matheson et al ). In addition, Proteobacteria , which includes a wide variety of pathogens (such as Escherichia , Salmonella , Vibrio , Helicobacter and Yersinia ), is associated with inflammation (Cordonnier et al ; Wang et al ).…”
Section: Discussionmentioning
confidence: 67%
“…A recent study found that the relative abundance of Firmicutes is associated with energy intake from the diet (Turnbaugh et al ); a higher proportion of the Firmicutes phylum was found in obese children and adults than lean individuals. In the present study, the lower relative abundance of Bacteroidetes and Firmicutes in IUGR piglets than controls suggests that IUGR piglets are less efficient at extracting energy from their diet and consequently gain less weight (Matheson et al ). In addition, Proteobacteria , which includes a wide variety of pathogens (such as Escherichia , Salmonella , Vibrio , Helicobacter and Yersinia ), is associated with inflammation (Cordonnier et al ; Wang et al ).…”
Section: Discussionmentioning
confidence: 67%
“…Large litters are often including more reduced-birthweight piglets with characteristics of IUGR (Matheson et al, 2018;Yuan et al, 2015) showing physiological dysfunctions including hypoglycaemia, temperature instability, and increased neonatal morbidity and mortality (Aucott, Donohue, & Northington, 2004). IUGR piglets are characterized by a low birthweight and a dolphin-like head conformation (Hales, Moustsen, Nielsen, & Hansen, 2013).…”
Section: Intr Auterine G Row Th Re S Tri C Ti On (I Ug R ) Pi G Le Tsmentioning
confidence: 99%
“…Large litters have a direct impact also on piglets at birth. The higher is the number of piglet born in a litter, the lower is the piglet birthweight ( Figure 2) and the higher is the variation in piglet birthweight within the litter (Akdag, Arslan, & Demir, 2009;Beaulieu, Aalhus, Williams, & Patience, 2010;Matheson, Walling, & Edwards, 2018;Quesnel, Brossard, Valancogne, & Quiniou, 2008;Smit et al, 2013). A greater number of piglets born than the available teats at the sow's udder, a lower birthweight and a greater birthweight variation all increase the piglets' competition for colostrum intake (Declerck, Sarrazin, Dewulf, & Maes, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, hyperprolific sows give birth to more piglets with low birth weight and with signs of intrauterine growth restriction (IUGR). There is an inverse relationship between number of piglets born in a litter and piglet birth weight; large litters are also associated with high variation in piglet birth weight within the litter (Quesnel et al, 2008;Akdag et al, 2009;Beaulieu et al, 2010;Smit et al, 2013;Matheson et al, 2018). A greater number of piglets born than the available teats at the sow's udder, lower birth weight and greater birth weight variation increase piglet competition for colostrum intake (Declerck et al, 2017).…”
Section: Improving Colostrum Intakementioning
confidence: 99%